An Interreligious Dispute on the Controversial Case of Elia Myron’s Correction to Tafsir: An Analysis Based on Kim Knott’s Framework - Zulfikar, Eko; Hafizh, Azhar Amrullah; Fithrotul Aini, Adrika; Tambunan, Syafrianto; M. Inthizam, Kemas (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This article examines the concept of religious tolerance through Qur’anic exegesis, applying the insider–outsider framework introduced by Kim Knott. The study is prompted by a social fact that has generated public controversy and gone viral, namely the request by Elia Myron, a Christian, to Indonesia’s Ministry of Religious Affairs to conduct a re-examination of the interpretation of Surah al-A‘raf [7]:157. Employing a qualitative research design, the study uses content analysis grounded in the insider–outsider approach to evaluate the discourse and responses arising from the issue. The findings indicate that applying the insider–outsider perspective to Elia Myron’s open letter to the Ministry of Religious Affairs, which calls for a review of Qur’anic exegesis, has the potential to provoke tensions and deepen divisions among religious communities in Indonesia. From an outsider’s standpoint, Elia’s action is widely supported and perceived as a manifestation of tolerance by the majority of Christians, as the request specifically emphasizes revisiting the exegesis of Surah al-A‘raf [7]:157, which includes references to the Torah and the Bible. However, from the insider standpoint, the action is interpreted as encroaching too deeply on Islamic teachings and is therefore seen as neglecting a key indicator within the discourse of religious moderation, namely tolerance, as underscored by Indonesia’s Ministry of Religious Affairs. In addition, several social media posts related to Elia’s request to review the Qur’anic exegesis are found to have explicitly served as early triggers for discourse containing intolerant elements, thereby potentially undermining harmonious relations among religious communities, particularly between Muslims and Christians.